2019
DOI: 10.3390/molecules24050994
|View full text |Cite
|
Sign up to set email alerts
|

Differential Proteomics Reveals miR-155 as a Novel Indicator of Liver and Spleen Pathology in the Symptomatic Niemann-Pick Disease, Type C1 Mouse Model

Abstract: Niemann-Pick disease, type C1 (NPC1) is a rare, autosomal recessive, lipid storage disorder caused by mutations in NPC1. As a result, there is accumulation of unesterified cholesterol and sphingolipids in the late endosomal/lysosomal system. Clinically, patients can present with splenomegaly and hepatomegaly. In the current study, we analyzed the differential proteome of the spleen in symptomatic Npc1−/− mice to complement previous studies focused on the differential proteome of the liver, and then evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 51 publications
2
11
0
Order By: Relevance
“…The pathway analysis indicates that many differentially expressed proteins belong to canonical pathways such as those involved in autophagy, phagosome maturation, and iron homeostasis. Our results are in agreement with previous reports showing that these processes (autophagy [21,33], phagosome maturation [34] and iron homeostasis) are altered in different NPC models [21,[33][34][35].…”
Section: Differentially Expressed Proteins In Npc1 Deficient Hepatocytes Are Predominantly Related To Alterations In Metabolism and Liversupporting
confidence: 94%
See 1 more Smart Citation
“…The pathway analysis indicates that many differentially expressed proteins belong to canonical pathways such as those involved in autophagy, phagosome maturation, and iron homeostasis. Our results are in agreement with previous reports showing that these processes (autophagy [21,33], phagosome maturation [34] and iron homeostasis) are altered in different NPC models [21,[33][34][35].…”
Section: Differentially Expressed Proteins In Npc1 Deficient Hepatocytes Are Predominantly Related To Alterations In Metabolism and Liversupporting
confidence: 94%
“…Using MS-based approaches, the authors showed that high mannose and sialylated N-glycans were altered, with a potential role in the lysosomal impairments observed in NPCD [19]. Interestingly, previous reports have already shown differential liver proteome in the NPC1 mouse model using whole liver tissue [20,21]. The hepatocytes are the main cells involved in liver metabolism, and account for approximately 78% of liver tissue volume [22,23].…”
Section: Of 15mentioning
confidence: 99%
“…We have recently reported altered expression in late endosomal/lysosomal proteins, Limp2 and Rab7a, using differential proteomics in the liver of symptomatic Npc1 −/− mice . Additionally, we show microRNA‐155 is elevated in the liver of symptomatic Npc1 −/− mice …”
Section: Introductionmentioning
confidence: 58%
“…All animal experiments were performed according to UIC Institutional Animal Care Committee‐approved protocols. Npc1 +/+ and Npc1 −/‐ mice (BALB/cNctr‐Npc1 m1N/m1N , Jackson Laboratories) were euthanized at 11 weeks of age ( N = 5 for each genotype and age) via CO 2 asphyxiation, decapitated, and liver tissue collected, flash frozen on dry ice, and stored at –80 °C, as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Finally, our results also showed an increase of miR‐155 in NLSDM patients in comparison to the control group. MiR‐155 has important functions in inflammation and, recently, was described to contribute to liver pathology and arteriosclerosis …”
Section: Discussionmentioning
confidence: 99%